Long-term consumption of hydrogen-rich water provides hepatoprotection by improving mitochondrial biology and quality control in chronically stressed mice - Qi He; Xiang Lan; Mengyuan Ding; Na Zhang (PLoS ONE, 2025)
Background Chronic stress has emerged as a prevalent facet of contemporary existence, significantly jeopardizing overall bodily health. The liver, a pivotal organ responsible for metabolic equilibrium, is particularly vulnerable to its adverse effects. This study delves into the hepatoprotective properties of extended consumption of HRW in mice subjected to chronic stress. Methods Mice subjected to chronic stress via CUMS and HRW administration for seven months underwent liver pathological examination. Key liver function indicators (AST, ALT), oxidative stress markers (SOD, CAT, GSH), and markers related to lipid peroxidation and ferroptosis (MDA, Fe) were measured using standard kits. ELISA determined corticosterone and 4-HNE levels. Immunofluorescence evaluated ROS, Nrf2, and apoptosis in liver tissues. Western blotting analyzed markers for ferroptosis (GPX4, SLC7A11, HO-1, Nrf2), apoptosis (Bax, Bcl-2, Cytc, Caspase-3, Caspase-8), mitochondrial biogenesis (Nrf1, PGC-1α, Tfam), and quality control (Drp1, Fis1, Mfn1, Mfn2, OPA1, PINK1, Parkin, LC3 I/II). Results The findings indicate a noteworthy improvement in liver health among mice exposed to HRW, as evidenced by histological analysis. Furthermore, the consumption of HRW exhibited hepatoprotection, as evidenced by the normalization of AST and ALT levels. Mechanistically, our results indicate that HRW elevates the levels of SOD, CAT, and GSH, while effectively clearing ROS within mitochondria. It was observed led to a regulation in the expression of mitochondrial quality control proteins, consequently improving mitochondrial biogenesis (Nrf1, PGC-1α, Tfam), and increasing ATP production. Furthermore, HRW decreased Cytc, Bax, Caspase-3, and Caspase-8 levels, and increasing the expression of Bcl-2. Additionally, HRW reduced MDA and 4-HNE levels, alleviating ferroptosis through the Nrf2/HO-1 pathway, and upregulating the expression of GPX4 and SLC7A11. By mitigating hepatocyte death through the aforementioned mechanisms, HRW fulfills its crucial role in safeguarding liver health. Conclusions This study reveals that long-term hydrogen-rich water (HRW) consumption provides significant hepatoprotection in mice under chronic stress. HRW normalizes liver enzyme levels, enhances antioxidant capacity, and reduces lipid peroxidation and ferroptosis. It improves mitochondrial biogenesis, function, and ATP production, and attenuates apoptosis by modulating related proteins. Behavioral tests show HRW alleviates stress-induced anxiety and enhances exploratory behavior. These findings suggest HRW is a promising non-invasive intervention for preventing and treating stress-related liver disorders by targeting oxidative stress and mitochondrial dysfunction.